Evaluation of the promotional efforts of newater. - Lim, Sze Lin. (2008)
We evaluate the effectiveness of these promotional efforts through our own perspective and the general public’s perspective. Through analyzing the results and the survey findings, we conclude on each promotional effort’s effectiveness and suggest ways to improve them. Eventually, we hope to increase the level of acceptance of Newater in Singapore.